Need for Cognitive Closure, Risk Aversion, Uncertainty Changes, and Their Effects on Investment Decisions. (June 2015) - Disatnik, David; Steinhart, Yael
Investment decisions play a crucial role in the way consumers manage their wealth, and therefore, it is important to understand how consumers make these decisions. This research contributes to this attempt by examining consumers' investment decisions in response to new information about changes in uncertainty in financial markets. The authors identify possible conditions under which consumers, despite having new information about changes in market uncertainty, are less likely to assimilate the new information and consequently do not make investment decisions that are in line with their risk-aversion levels. Specifically, in a series of studies, the authors show that high rather than low need for cognitive closure can lead to a lack of openness to new information and therefore may dilute consumers' tendency to update their investment portfolios in a way that reflects their risk preferences. In addition, the authors address possible ways to influence consumers' assimilation of new information, to help even those with high need for cognitive closure make investment decisions that are in line with their levels of risk aversion.